Population variation of the red stripe weevils, Rhynchophorus vulneratus (Coleoptera: Curculionidae) isolated by geographical limit - Siti Nurlydia, Sazali; Izfa Riza, Hazmi; Fatimah, Abang; Faszly, Rahim; Abdul Aziz, Jemain (National University of Singapore, 2019)
Morphological variation of the red stripe weevils, Rhynchophorus vulneratus (Coleoptera: Curculionidae) was investigated using three different populations from Kota Samarahan (Sarawak), Mukah (Sarawak), and central of Peninsular Malaysia. A total of 145 individuals were morphologically examined in which 23 morphological characters of head, body and legs were linearly measured. All data were analysed using Principal Component Analysis in Minitab Version 17.1. The first three principal components explained 82.5% of variance with eigenvalues greater than 1.0 and the principal component plot of PC1 against PC2 showed the clustering of the three populations, in which Mukah population forms its own cluster whereas Kota Samarahan and Peninsular Malaysia populations show overlapping clusters. The morphometric findings indicated that the pronotum and elytra were the most diagnostic characters for discriminating the three examined populations. This suggests that the populations of R. vulneratus might have undergone adaptive changes on its morphological characters possibly due to different environmental factors including the availability of food resources, habitat types,and human activities and this requires further testing.